Pengaruh Personality Psychopathy dan Narcissism Terhadap Radikalisme - Nawang Retno Dwiningrum; Zulkarnain, Zulkarnain (Universitas Nusantara PGRI Kediri, 2023)
The influence of dark personalities like psychopathy and narcissism has not been studied comprehensively in the study of radicalism and terrorism. Several recent research results reveal that it is very important to analyze and see radicalism with dark personalities, psychopathy, and narcissism. This study aims to determine the effect of psychopathy and narcissism on radicalism. Data were collected randomly through an online questionnaire filled out by 469 university students in Balikpapan City to test the direct effect of dark personality traits like psychopathy and narcissism on radicalism. The results of this study reveal that dark personality psychopathy has a direct effect on radicalism. Meanwhile, dark personalities suffer from psychopathy. Narcissism has no effect on radicalism, whereas dark personality psychopathy has an effect on radicalism. The findings of this study indicate that dark personality traits such as psychopathy and narcissism have direct and indirect effects on radicalism. Research findings are discussed, along with the implications of considering personality factors in the study of radicalism and terrorism.